Experimental study of wave energy converter arrays adapted to a semi-submersible wind platform - Kamarlouei, M. (2022)
The design of an offshore wind turbine floating platform seeks to minimize platform pitching motions that otherwise generate large accelerations and loads on the turbine, nacelle and blades, and decrease their lifetime. This objective is harder to achieve as the upscaling to more powerful wind turbines amplify the effects of pitching motions since the wind turbines’ height and mass are higher. Thus, innovative solutions to control the pitching motions should be developed. This study presents a solution based on a concentric array of wave energy converters which was originally designed to be attached on a floating platform to generate wave energy. Meanwhile, it was found that the concept may provide bigger restoring moments for platforms, amplified by its lever type arms, which are useful to control the pitching motions. Thus, a wind thrust simulator is adapted to the original experimental model and tests performed to understand the advantage of using these converters in the control of the pitching motions of a wind turbine platform. The experimental results indicate that platform motions are controllable by the wave energy converters however must be optimized to achieve better performance. These results also provide some design knowledge to test the concept at bigger rated power wind turbines.